2021
DOI: 10.21203/rs.3.rs-806033/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-intensity Physical Activity Is Not Associated With Better Cognition in the Elder: Evidence From the China Health and Retirement Longitudinal Study

Abstract: Objective To evaluate the association of physical activity (PA) intensity with cognitive performance at baseline and during follow up. Methods A total of 4 039 participants aged 45 years or above from the China Health and Retirement Longitudinal Study were enrolled in visit 1 (2011-2012), and followed for cognitive function in visit 2 (2013-2014), visit 3 (2015-2016) and visit 4 (2017-2018). We analyzed the association of PA intensity with global cognition, episodic memory and mental intactness at baseline usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…First, the disease diagnosis history in the CHARLS was self-reported. However, it has been reported that self-reported cardiovascular diseases were highly consistent with medical records (43,44). Second, the outcome in this study is diagnosis history of any stroke.…”
Section: Discussionmentioning
confidence: 57%
“…First, the disease diagnosis history in the CHARLS was self-reported. However, it has been reported that self-reported cardiovascular diseases were highly consistent with medical records (43,44). Second, the outcome in this study is diagnosis history of any stroke.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, they may not engage in various kinds of exercises for body building like their urban counterparts, but may have more daily productive physical activities (Cai et al, 2012). One recent study (Wu et al, 2021) revealed that the cognitive benefits of exercise also depend on its intensity: Whereas mild and moderate physical activity was associated with better cognitive performance, vigorous physical activity was not. So future studies may continuously explore rural/urban differences by separating the exercise and productive physical activities and additionally considering their intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to report their usual weekly PA information based on the IPAQ. Specifically, PA was divided into vigorous PA (VPA), moderate PA (MPA) and light PA (LPA), and described in various dimensions (intensity, duration, frequency and volume; Wu et al, 2021). Considering that the World Health Organization (2020) reports that 1 min of vigorous activity is equal to 2 min of moderate intensity activity (1).…”
Section: Physical Activitymentioning
confidence: 99%